The Influence of Principals’ Interpersonal Communication on Teacher Performance in Integrated Islamic Elementary Schools - M. Abdul Somad; Oman Fathurohman; Efrita Norman; Lina Marliani; Jalaludin Jalaludin; Vasavvi Acharjya (Jurnal Pendidikan Islam, 2026)
Effective leadership in Islamic elementary schools is a crucial issue, as principals’ interpersonal communication plays a central role in shaping teacher professionalism, motivation, and instructional performance. This study examines the influence of principals’ interpersonal communication on teacher performance in Integrated Islamic elementary schools (IIES) in Indonesia. The research employed a quantitative approach using an ex-post facto survey design, with data analyzed through correlation and regression techniques. Questionnaires were administered to 78 teachers selected through random sampling, and the data were processed using SPSS version 25. The results demonstrate that principals’ interpersonal communication has a significant, positive, and very strong effect on teacher performance, accounting for 79.3% of the variance, while the remaining 20.7% is influenced by other factors not explored in this study. The regression analysis produced the equation Y = 16.111 + 1.845X, indicating that improvements in interpersonal communication are associated with substantial increases in teacher performance. The findings also suggest that clear, supportive, and collaborative communication practices foster a more productive and professional teaching environment. These results imply that strengthening principals’ interpersonal communication competencies is a strategic priority for improving teacher performance and enhancing the quality of Islamic education in elementary schools.